A SWOT Analysis of Rann Utsav Kutch (Gujarat): Unveiling the Strengths, Weaknesses, Opportunities, and Threats of Rann Utsav Kutch (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The paper is aimed to describe one of the most famous tourist destinations of the country, Rann Utsav. The fair has much strength like handicrafts, traditional cuisine, traditional hut etc. and also have some weakness like lack of basic amenities. Here the researcher identifies strength and weakness of Rann Utsav. Future is uncertain but in planning process detection of opportunities and threats can sustain this fair for long time.